The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1515/text.1.1986.6.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Scripts for school: Cross-cultural communication in elementary classrooms

Abstract: This study reports on successful and unsuccessful efforts at communication between teachers and students who do not share a common language. A topdown processing model is proposed to account for the phenomena, with scripts the highest level and code the lowest. Significantly, commonalities in scripts allowed Interpretation of meaning with minimal understanding of linguistic forms. Conversely, communication was impeded by cultural differences in scripts for school, including setting, roles and responsibilities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Some scholars studied the impact of incorporating regional cultural elements into English teaching on English learning effectiveness and cross-cultural communication ability. For example, Saville-Troike [5] studied the influence of American culture on English language teaching and proposed corresponding teaching strategies and methods. Kramsch [6] discussed the relationship between cultural factors and language teaching from the perspective of cultural context and proposed some effective English teaching methods and strategies.…”
Section: Research Trends Of Integrating Cultural Elements Into Colleg...mentioning
confidence: 99%
“…Some scholars studied the impact of incorporating regional cultural elements into English teaching on English learning effectiveness and cross-cultural communication ability. For example, Saville-Troike [5] studied the influence of American culture on English language teaching and proposed corresponding teaching strategies and methods. Kramsch [6] discussed the relationship between cultural factors and language teaching from the perspective of cultural context and proposed some effective English teaching methods and strategies.…”
Section: Research Trends Of Integrating Cultural Elements Into Colleg...mentioning
confidence: 99%
“…But there could also be other explanations. Saville-Troike & Kleifgen (1986) have investigated and analyzed the communication in a public elementary school that serves children from a variety of language backgrounds and they have organized their findings into three levels of interaction: scripts, structures and codes. The category of scripts included rules and expectations for behavior and they found that "the most serious miscommunication between teachers and students occurred where their scripts included conflicting rules and expectations for classroom behavior".…”
Section: Examples Of Socio-cultural Miscommunicationmentioning
confidence: 99%
“…Anlamlı etkileşimler oluşturmak için sadece gramatik olarak doğru dil kullanımının önemli olmadığı da araştırmalarda gösterilmiştir. Saville-Troike ve Kleifgen (1986), anasınıfı ve ilköğretim sınıflarında İngilizceyi ikinci dil olarak öğrenen çocukların öğretmenleri ve akranları ile yaptıkları çokdilli diyalogları inceledikleri çalışmalarında, sınıf ortamındaki birbiriyle uyumlu (tutarlı) söylemlerin ve eylemlerin yorumlanmasının, katılımcıların ortak yaşantılarına ve paylaştıkları genel kültüre, önceki söylemlerin şimdiki zamana uyarlanmasına ve katılımcıların diğerlerinin eylemlerini uygun sınıf etkinliği çerçevesinde anlamlandırmalarına bağlı olduğunu gözlemlemişlerdir.…”
Section: çOkmodluluk Ve İkinci Dil Kazanımının İlk Evrelerinde Anlamın Yeniden İnşasıunclassified